The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1242/dev.101196
|View full text |Cite
|
Sign up to set email alerts
|

TRIP/NOPO E3 ubiquitin ligase promotes ubiquitylation of DNA polymerase η

Abstract: We previously identified a Drosophila maternal effect-lethal mutant named 'no poles' (nopo). Embryos from nopo females undergo mitotic arrest with barrel-shaped, acentrosomal spindles during the rapid cycles of syncytial embryogenesis because of activation of a Chk2-mediated DNA checkpoint. NOPO is the Drosophila homolog of human TNF receptor associated factor (TRAF)-interacting protein (TRIP), which has been implicated in TNF signaling. NOPO and TRIP contain RING domains closely resembling those of known E3 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 81 publications
9
42
1
Order By: Relevance
“…S4 B). Moreover, although overexpression of TRA IP WT stimulated polη polyubiquitylation as previously reported (Wallace et al, 2014), this depended neither on its RING nor PIP domains (Fig. S4 C), and depletion of TRA IP did not reduce polη ubiquitylation levels (Fig.…”
Section: Roles Of Tra Ip Ubiquitin Ligase Activity and Pcna Binding Isupporting
confidence: 82%
See 4 more Smart Citations
“…S4 B). Moreover, although overexpression of TRA IP WT stimulated polη polyubiquitylation as previously reported (Wallace et al, 2014), this depended neither on its RING nor PIP domains (Fig. S4 C), and depletion of TRA IP did not reduce polη ubiquitylation levels (Fig.…”
Section: Roles Of Tra Ip Ubiquitin Ligase Activity and Pcna Binding Isupporting
confidence: 82%
“…TRA IP has recently been linked to other genome integrity maintenance processes, including TLS through ubiquitylation of the TLS polymerase polη and in the spindle assembly checkpoint (Chapard et al, 2014;Wallace et al, 2014). However, we found that these involvements were unlikely to explain the requirement of TRA IP in genome maintenance after replication stress.…”
Section: Roles Of Tra Ip Ubiquitin Ligase Activity and Pcna Binding Icontrasting
confidence: 54%
See 3 more Smart Citations